Pencegahan korupsi politik: Penerapan Sistem Integritas Partai Politik di Partai Kebangkitan Bangsa - Aditya Perdana; Muhammad Hanifuddin (Integritas: Jurnal Antikorupsi, 2023)
This paper focuses on examining the institutionalization of the Political Party Integrity System (SIPP) which was pushed by the Corruption Eradication Commission (KPK) as part of efforts to prevent political corruption in the National Awakening Party (PKB). Since the 2009, 2014 and 2019 elections, PKB's vote share has increased. The number of party cadres who were caught in corruption cases was relatively small compared to other parties. The main question to be answered is how the institutionalization of SIPP in PKB was initiated by the KPK as part of efforts to prevent political corruption? The theoretical framework used is O'Donnell's institutionalization theory. There are two stages of institutionalization; the spread of values (value infusion) and routine actions against these values (behavioral routineization). Data was collected through literature review and interviews. This research shows that the institutionalization of SIPP in PKB takes place through the stage of spreading SIPP values. This distribution is contained in Mabda' Siyasi, AD/ART, PKB Manifesto, and Party Regulations. It regulates the code of ethics, regeneration and recruitment, internal democratization, and financial governance. The next stage is getting used to the internal provisions of this PKB in carrying out party activities. PKB is one of the parties that welcomes the existence of SIPP. For PKB, SIPP is an acceleration to strengthen party integrity. Become a concrete step to prevent political corruption involving party cadres.